Pragmatic and Syntactic Features of Topics in American Sign Language - Janzen, Terry (Meta, 1997)
AbstractAmerican Sign Language (ASL) sentences are understood as constructed around a topic-comment, rather than a subject-predicate, relation, but topic constituents are not well understood. This study examines topic-marked constituents in the context of discourse negotiation, suggesting that there are two sources for semantic material that is coded as topics in ASL. These are first, pragmatic contexts that are external to the discourse event, and second, the syntactic structure of the discourse itself. This study is based on two ASL narrative texts which were coded for topic and non-topic constituents and seeks to familiarized the interpreter with the grammatical structure of ASL. This way, the interpreter has a better grasp of the signer's perspective on the information coded both by topics and non-topics in the discourse.